Business Process Reengineering to Excellence Warehouse Management System: A Case Study of Retail Industry - Devi Natasha Polim; Yuliani Dwi Lestari (CV. Syntax Corporation Indonesia, 2023)
Company X is a modern Indonesian retail company that faces stock inaccuracies continuously and the variances exceeds the limit set by the company that reduce its profits continuously. Variances are difficult to identify since the stock recording in company X is not separated between stock in the warehouse and the store and not using warehouse management system. Business process re-engineering will be carried out by proposed two alternatives using traceability technology for the warehouse management system. Standard operating procedures will also be developed and used as a guide in implementing the system. This study uses qualitative method from a semi-structured interview with the management team, observation, and focus group discussion. The data were analyzed with gap analysis, cause mapping, and analytical hierarchy process to select the proposed alternatives using QR Code and RFID. The results from data processing is show that the company select QR Code as the technology used.